Canadian School Psychology and Indigenous Peoples: Opportunities and Recommendations. (March 2023) - Bernett, Payton; Spence, Sara; Wilson, Candace; Gurr, Erin; Zentner, Daysi; Wendt, Dennis C.
School psychologists play important roles in working alongside Indigenous Peoples within Canada; however, a large gap exists between the discipline's actions and the recommendations set forth by Indigenous Nations and governmental working groups. In this conceptual article, we seek to highlight the need for further Indigenous representation and engagement in the field of school psychology, as well as present key areas of relevance. We first briefly contextualize the relationship between Indigenous Peoples and school psychology, followed by the results of a brief survey concerning Indigenous representation and engagement across five school psychology doctoral programs in Canada. Next, we discuss nine key areas of consideration for school psychologists based on the Calls to Action of the Truth and Reconciliation Commission of Canada and the Calls for Justice of the National Inquiry into Missing and Murdered Indigenous Women and Girls. Each area of consideration provides school psychologists with a starting point for concrete actions when working with Indigenous students, families, and communities.